Electronic-vibrational density evolution in a perylene bisimide dimer: mechanistic insights into excitation energy transfer. Issue 29 (21st July 2021) - Kundu, Sohang; Makri, Nancy
Abstract : Mechanistic picture of excitation energy transfer through the time evolution of electronic-vibrational densities in a perylene bisimide dimer from all-mode real-time path integral calculations. Abstract : The process of excitation energy transfer (EET) in molecular aggregates is etched with the signatures of a multitude of electronic and vibrational time scales that often are extremely difficult to resolve. The effect of the motion associated with one molecular vibration on that of another is fundamental to the dynamics of EET. In this paper we present simple theoretical ideas along with fully quantum mechanical calculations to develop a comprehensive mechanistic picture of EET in terms of the time evolution of electronic-vibrational densities (EVD) in a perylene bisimide (PBI) dimer, where 28 intramolecular normal modes couple to the ground and excited electronic states of each molecule. The EVD motion exhibits a plethora of dynamical features, which impart physical justification for the composite effects observed in the EET dynamics. Weakly coupled vibrations lead to classical-like motion of the EVD center on each electronic state, while highly nontrivial EVD characteristics develop under moderate or strong exciton–vibration interaction, leading to the formation of split or crescent-shaped densities, as well as density retention that slows down energy transfer and creates new peaks in the electronic populations. Pronounced correlation effects are observed in two-mode projections of the EVD, as a consequence of indirect vibrational coupling between uncoupled normal modes induced by the electronic coupling. Such indirect coupling depends on the strength of exciton–vibration interactions as well as the frequency mismatch between the two modes and leaves nontrivial signatures in the electronic population dynamics. The collective effects of many vibrational modes cause a partial smearing of these features through dephasing.